Answer:
Value of expression 1 = 3
Value of expression 2 = 42
Value of expression 3 = 15
Value of expression 4 = 2
Step-by-step explanation:
Expression 1 : the sum of m and 3 divided by the difference of m minus 3
Expression 1![: \frac{m+3}{m-3}](https://tex.z-dn.net/?f=%3A%20%5Cfrac%7Bm%2B3%7D%7Bm-3%7D)
Substitute m = 6
So, value of expression 1=![\frac{6+3}{6-3}=3](https://tex.z-dn.net/?f=%5Cfrac%7B6%2B3%7D%7B6-3%7D%3D3)
Expression 2 : the sum of 3 times m and 4 times m
Expression 2: 3m+4m
Substitute m = 6
So, value of expression 2=3m+4m=3(6)+4(6)=42
Expression 3 : the difference of the product of 3 and m minus the quotient of m divided by 2
Expression 3:![3m-\frac{m}{2}](https://tex.z-dn.net/?f=3m-%5Cfrac%7Bm%7D%7B2%7D)
Substitute m = 6
So, value of expression 2= ![3m-\frac{m}{2}=3(6)-\frac{6}{2}=15](https://tex.z-dn.net/?f=3m-%5Cfrac%7Bm%7D%7B2%7D%3D3%286%29-%5Cfrac%7B6%7D%7B2%7D%3D15)
Expression 4 :the quotient of 6 divided by the difference of m minus 3
Expression 4:![\frac{6}{m-3}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7Bm-3%7D)
Substitute m = 6
So, value of expression 4=![\frac{6}{m-3}=\frac{6}{6-3}=2](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7Bm-3%7D%3D%5Cfrac%7B6%7D%7B6-3%7D%3D2)